Contributors to Depressive Symptoms among Korean Immigrants with Type 2 Diabete - Choi, Sarah E. (2013)
BACKGROUND: Patients with diabetes have a higher prevalence of depression than the general population. Korean immigrants with type 2 diabetes are understudied. OBJECTIVES: To identify the prevalence and correlates of depressive symptoms in Korean immigrants. METHOD: In this cross-sectional descriptive study, a community sample of 164 Korean immigrant adults with type 2 diabetes were assessed for depressive symptoms using the Center for Epidemiological Studies-Depression scale. Predictors of depression were grouped into three categories: demographic (age, gender, education, English proficiency); clinical (duration of diabetes, comorbidities, insulin use); and psychosocial (general health, diabetes-related quality-of-life, family support). RESULTS: Approximately 56% of participants had CES-D scores ≥ 16. Higher levels of depression were associated with greater impact of diabetes on QOL (b = 5.68, p = .001), worse overall health (b = -0.09, p = .012), and less family support (b = -4.02, p = .042). The relationship between depression and diabetes impact on quality-of-life was stronger for men than women (b = 6.67, p = .020). DISCUSSION: Depressive symptoms are common among Korean immigrants with type 2 diabetes. Assessing diabetes-related quality-of-life, general health, and family support may be of value in better understanding depressive symptoms among this population. Among Korean immigrant men with type 2 diabetes, specific attention should be paid to diabetes-related quality-of-life.